2014
DOI: 10.30750/ijpbr.2.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological responses of a high yielding groundnut cultivar (Arachis hypogaea L. cv. K-134 ) under water stress

Abstract: The present study was undertaken to ascertain the morphological responses of a groundnut cultivar K-134, under different water stress regimes characterized as control, mild, moderate and severe stress represented by 100, 75, 50 and 25% soil moisture levels respectively for eight days. Root length increased over control at mild, moderate stress treatments and inhibited at severe stress conditions on all days of sampling. Severe stress treatments had caused significant inhibition in shoot growth on day-4 and 8. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…Depletion ratio generally affected the growth (plant height and the number of branches) of peanuts, the reduction in plant height with high depletion percentage could be attributed to a lower crop growth rate and the decrease in relative water content. These results agree with those of Madhusudhan and Sudhakar (2014) and Mourad, (2014). It is important to note that a higher number of branches in plants is desirable because it produces a higher yield, the decrease in the number of branches due to the lack of moisture content may be due to minimizing the shoot system of peanuts under dry conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Depletion ratio generally affected the growth (plant height and the number of branches) of peanuts, the reduction in plant height with high depletion percentage could be attributed to a lower crop growth rate and the decrease in relative water content. These results agree with those of Madhusudhan and Sudhakar (2014) and Mourad, (2014). It is important to note that a higher number of branches in plants is desirable because it produces a higher yield, the decrease in the number of branches due to the lack of moisture content may be due to minimizing the shoot system of peanuts under dry conditions.…”
Section: Discussionsupporting
confidence: 93%
“…At recovery stage, plant height of all genotypes did not recover with that of respective controls and genotype Dharani maintained higher plant height at control (18.4 cm plant -1 ) as well as stress release (14 cm plant -1 ) conditions. Our results are in line with earlier reports of decreased shoot growth in groundnut due to moistures stress (Madhusudhan and Sudhakar, 2014a). Baroowa et al (2012) also reported that plant height reduced in black gram and green gram genotypes due to moisture stress and their recovery not up to the control in these two crops.…”
Section: Effect Of Moisture Stress On Growth and Dry Matter Productionsupporting
confidence: 93%
“…Rapid root growth into the surrounding soil would have an adaptive advantage to utilize the soil water more completely. The findings of Reddy et al (2003), Thiyagarajan et al (2009) and Madhusudhan and Sudhakar (2014)…”
Section: Root Length and Root Volumementioning
confidence: 88%